2022
DOI: 10.3390/cells11081338
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib in the Treatment of Solid Tumors: Current State of Knowledge and Future Directions

Abstract: Bruton’s Tyrosine Kinase (BTK) is considered crucial in the activation and survival of both physiological and malignant B-cells. In recent years, ibrutinib, an oral BTK inhibitor, became a breakthrough therapy for hematological malignancies, such as chronic lymphocytic. However, ibrutinib’s feasibility might not end there. Several other kinases with established involvement with solid malignancies (i.e., EGFR, HER2) have been found to be inhibited by this agent. Recent discoveries indicate that BTK is a potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 138 publications
0
15
0
Order By: Relevance
“…Ibrutinib inhibits B-cell signaling and is used to treat B-cell malignancies but has also shown activity toward solid tumors due to its ability to inhibit multiple kinases. 32 Furthermore, since the primary tumor in our study was strongly growth-inhibited by the NPD incorporating 90 Y-AuNPs, this made it difficult to detect enhancement in effectiveness when combined with anti-PD-L1 antibodies. The reason for the modest primary tumor growth inhibition by NPD incorporating unlabeled AuNPs is not known, but AuNPs have been to inhibit the growth of ovarian cancer tumors in mice by inhibiting mitogen-activated protein kinase signaling.…”
Section: ■ Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Ibrutinib inhibits B-cell signaling and is used to treat B-cell malignancies but has also shown activity toward solid tumors due to its ability to inhibit multiple kinases. 32 Furthermore, since the primary tumor in our study was strongly growth-inhibited by the NPD incorporating 90 Y-AuNPs, this made it difficult to detect enhancement in effectiveness when combined with anti-PD-L1 antibodies. The reason for the modest primary tumor growth inhibition by NPD incorporating unlabeled AuNPs is not known, but AuNPs have been to inhibit the growth of ovarian cancer tumors in mice by inhibiting mitogen-activated protein kinase signaling.…”
Section: ■ Discussionmentioning
confidence: 88%
“…similarly found that treatment of 4T1 tumors in Balb/c mice with anti-PD-L1 antibodies alone was ineffective, but combining checkpoint immunotherapy with the Bruton’s tyrosine kinase inhibitor, ibrutinib , improved tumor response. Ibrutinib inhibits B-cell signaling and is used to treat B-cell malignancies but has also shown activity toward solid tumors due to its ability to inhibit multiple kinases . Furthermore, since the primary tumor in our study was strongly growth-inhibited by the NPD incorporating 90 Y-AuNPs, this made it difficult to detect enhancement in effectiveness when combined with anti-PD-L1 antibodies.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, the role of ABC transporters in cancer responses to ANT-containing chemotherapy has been suggested in DLBCL [ 70 ], MCL [ 71 ], and Burkitt lymphoma [ 72 ]. In addition to the primary indication of BTK inhibitors in CLL and lymphomas, their efficacy has recently been demonstrated in AML and solid tumours [ 73 , 74 , 75 , 76 ]. Rushworth et al (2014) discovered that BTK is phosphorylated (p-BTK), and is thus constitutively active in the majority of samples obtained from patients with AML.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, traditional chemotherapy may result in more mutations, which could result in the growth of additional cancers or the progression of treatment resistance in the initial tumor [56]. On the other hand, targeted therapies are created to block particular biochemical pathways in cancer cells that result in tumor cell death without harming DNA [57]. Enzymes called protein kinases catalyze the transfer of a phosphate group to a specific amino acid in a protein, altering the protein's functionality [58].…”
Section: Anticancer Properties Of Chalconesmentioning
confidence: 99%